Pemberdayaan Nelayan Dan UMKM melalui Diversifikasi Olahan Ikan Menuju â€œDesa Iwakâ€ dan Kawasan Minapolitan Di Desa Kalanganyar, Kec Sedati, Kabupaten Sidoarjo, Jawa Timur - Purwadi, Purwadi; Nugrono, Sigit Dwi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
Kalanganyar Village is a village in Sidoarjo Regency, Sedati District, which covers an area of 2/3 consisting of a pond, which borders the villages of Buncitan, Sawohan, Cemandi, and Tambakcemandi. Kalanganyar Village is one of the areas with socio-economic conditions that need to be improved. The source of the livelihood of the local community is very dependent on the results of fishing which is very influenced by the weather. When fishermen cannot go to sea due to extreme weather, local people do not have alternative sources of income. The problems with partners and the potential to support the Sedati sub-district as a Minapolitan area are (1) limited livelihoods of the community as fishermen, (2) The skills of the Fish Cultivation Group (Pokdakan) are still weak regarding the diversification of products made from fish as raw material, (3) There is still a lack of knowledge and practice regarding fish processing which has economic value. (4) Limited knowledge about the packaging of fish-based products (5) Lack of knowledge about marketing fish products. The method used is counseling and training, among others, the socialization of the importance of diversification of processed products made from fish, training on diversification of fish product processing technology, training on packaging of processed fish products, training on online and offline marketing management. The results achieved in implementing program activities (a). The community understands the importance of product diversification from fish so that fish has a high economic value, (b) Training on product diversification from fish is successful in making soy sauce from fish and shredded fish from milkfish, (c) Success in making soy sauce product packaging from fish and labeling jerky from milkfish , (d). Online marketing through social media and websites is still in the design process.